Neuropathology Training Worldwide—Evolution and Comparisons. (April 2014) - Del Bigio, Marc R.; Hainfellner, Johannes A.; McLean, Catriona A.; Powell, Suzanne Z.; Sikorska, Beata; Takahashi, Hitoshi; Weis, Joachim; Xuereb, John H.
Abstract Training of neuropathologists varies worldwide. Systems range from highly organized specialist and subspecialist education with national certification, to regulated training with diploma recognition, to informal apprenticeships in neurological hospitals and no formal recognition. This overview compiles and summarizes the history of regulated training systems, the status of neuropathology within various countries' medical systems and the manner in which neuropathologists are trained. Anecdotal evidence suggests that countries with regulated systems of neuropathology training and an active professional organization are more likely to have an adequate supply of diagnostic specialists and a vibrant research community. The different training systems reflect the style of medical services delivery in the respective countries. In general, the existence of formal neuropathology training systems occurs only in countries with relatively high levels of per capita health expenditures, reflecting the development of medical specialization overall. Evolving diagnostic technologies and major international research endeavors, whose goals are to understand structure and function of the human brain, demand that neuropathology training is more than simply diagnostic histopathology.